(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores how medical terminology has entered and reshaped Uzbek-language media over the past three decades. Drawing on corpus data from national newspapers, broadcast transcripts, and leading social-media channels, it maps the diffusion of specialist health lexis into public-facing genres, highlighting three intertwined drivers: (1) accelerated science-communication efforts during global health crises, (2) the growing influence of Russian and English source texts on Uzbek journalism, and (3) audience demand for comprehensible but authoritative explanations of complex medical topics. By triangulating quantitative term-frequency analysis with close reading of emblematic headlines, the study reveals a gradual shift from literal transliteration of Latin-based terms toward adaptive hybrid formations that better fit Uzbek phonology and word-formation norms. The findings shed light on broader questions of linguistic modernisation, terminological planning, and public health literacy in a digitally mediated society.